Judicial Protection in the Field of Public Procurement: The Transposition into Dutch Law of Directive 2007/66/EC Amending the Remedies Directives - Berends, Wouter-Jan (Utrecht Journal of International and European Law, 2010)
Public procurement procedures in the EU are coordinated by Directives 2004/17/EC and 2004/18/EC. The acquis communautaire provides minimum requirements for review procedures against public procurement decisions in order to ensure access to effective remedies for economic operators. These minimum requirements are established in Directives 89/665/ EEC and 92/13/EEC and recently amended by Directive 2007/66/EC. The Helby report identified several substantive concerns over the Dutch proposal on the implementation the of the Remedies Directive; Wet implementatie rechtsbeschermingsrichtlijnen. Although the transposition target date has not been met, the Dutch legislature has succeeded to transpose Directive 2007/66/EC into Dutch law while addressing the concerns of the Helby report.